Environmental DNA (eDNA) contamination patterns of African swine fever virus (ASFV) in swine transport vehicles in the Philippines - MJ Bartolome; LAM Aguirre; CM Poliquit; I Besas; JG Angeles; J Rabajante; S Camba; F Del Valle; A Ambrocio; F Caguicla; MG Bustamante; D Umali (Veterinární Medicína)
Since its introduction in 2019, African swine fever (ASF) has spread to all regions of the Philippines, affecting 73 out of its 82 provinces. To assess the environmental DNA (eDNA) contamination patterns of the ASF virus (ASFV) in swine transport vehicles and evaluate its measures of association, a total of 450 environmental swabs from 30 transportation vehicles were tested using qPCR. Five out of 30 vehicles (16.67%) tested positive in at least one of the following areas: cargo area or sidecar walls (6.67%), cargo area or sidecar floors (6.67%), hauling personnel's hands (6.67%), steering wheel or handlebars (3.33%), gear shift levers (3.33%), floor mats or footpegs (3.33%), dashboards (3.33%), door handles or sidecar gate bolts (3.33%), tyres/wheels (3.33%), fenders (3.33%), and hauling personnel's footwear (3.33%). All investigated risk factors were analysed using Chi-square, Fisher's exact test, and odds ratio and were found to be insignificant, including the frequency of swine transportation per week, frequency of cleaning per week, cleaning materials used, disinfection practices, the number of pigs transported, and whether hauliers owned pigs (p > 0.05). This study illuminates the environmental contamination patterns of ASFV in swine transport vehicles, underscoring the need for targeted biosecurity protocols in areas with a high risk of contamination, particularly the cabin areas. More effective vehicle disinfection systems that will not damage equipment or pose health risks to hauliers are recommended to reduce the risk of ASF disease transmission between countries and geographic regions.